Effect of gender, facial dimensions, body mass index and type of functional occlusion on bite force - KOÇ, Duygu (J Appl Oral Sci, 2011)
OBJECTIVE: Some factors such as gender, age, craniofacial morphology, body structure, occlusal contact patterns may affect the maximum bite force. Thus, the purposes of this study were to determine the mean maximum bite force in individuals with normal occlusion, and to examine the effect of gender, facial dimensions, body mass index (BMI), type of functional occlusion (canine guidance and group function occlusion) and balancing side interferences on it. MATERIAL AND METHODS: Thirty-four individuals aged 19-20 years-old were selected for this study. Maximum bite force was measured with strain-gauge transducers at first molar region. Facial dimensions were defined by standardized frontal photographs as follows: anterior total facial height (ATFH), bizygomathic facial width (BFW) and intergonial width (IGW). BMI was calculated using the equation weight/height(2). The type of functional occlusion and the balancing side interferences of the subjects were identified by clinical examination. RESULTS: Bite force was found to be significantly higher in men than women (p<0.05). While there was a negative correlation between the bite force and ATFH/BFW, ATFH/IGW ratios in men (p<0.05), women did not show any statistically significant correlation (p>0.05). BMI and bite force correlation was not statistically significant (p>0.05). The average bite force did not differ in subjects with canine guidance or group function occlusion and in the presence of balancing side interferences (p>0.05). CONCLUSIONS: Data suggest that bite force is affected by gender. However, BMI, type of functional occlusion and the presence of balancing side interferences did not exert a meaningful influence on bite force. In addition, transverse facial dimensions showed correlation with bite force in only men.